1993
DOI: 10.1002/yea.320090508
|View full text |Cite
|
Sign up to set email alerts
|

Increased transformation levels in intact cells of Saccharomyces cerevisiae aculeacin A‐resistant mutants

Abstract: Several Saccharomyces cerevisiae mutants resistant to the cell wall synthesis inhibitor aculeacin A exhibit higher transformation levels than the parental strain. Mutant acr2 has been studied in more detail. It is transformed up to ten-fold more efficiently than the wild-type strain with episomal, centromeric and integrative plasmids, and dimethyl sulfoxide has an additive effect improving transformation efficiency. Transformation with linear DNA molecules is not as much affected in acr2 cells. The observed ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

1994
1994
2015
2015

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
0
3
0
2
Order By: Relevance
“…22.1B 2 ). We now know that the successful alteration of both chemical and physical properties of the cell wall is dependent on the action of certain genes (see Genes responsible for yeast competence ; Gallego et al 1993 ;Durand et al 1993 ;Tomlin et al 2000 ; ) and environmental factors (PEG, cations, heat shock, and carrier DNA) expected or known to alter cell wall properties (Brzobohatý and Kováč 1986 ;Bruschi et al 1987 ;.…”
Section: Crossing the Cell Wallmentioning
confidence: 99%
See 1 more Smart Citation
“…22.1B 2 ). We now know that the successful alteration of both chemical and physical properties of the cell wall is dependent on the action of certain genes (see Genes responsible for yeast competence ; Gallego et al 1993 ;Durand et al 1993 ;Tomlin et al 2000 ; ) and environmental factors (PEG, cations, heat shock, and carrier DNA) expected or known to alter cell wall properties (Brzobohatý and Kováč 1986 ;Bruschi et al 1987 ;.…”
Section: Crossing the Cell Wallmentioning
confidence: 99%
“…Several gene products affecting transformation are connected to this (Table 22.2 ). They are involved in regulating the function of endoplasmic reticulum (ER) and Ca 2+ homeostasis ( SPF1 ; , maintaining of cAMP level ( PDE2 ; Tomlin et al 2000 ;, and the synthesis of GDP-mannose during cell wall biosynthesis ( SRB1 ; Tomlin et al 2000 ) or ß-glucan synthesis ( acr mutants; Gallego et al 1993 ). SIN3 is possibly regulating many genes through histone deacetylation.…”
Section: Genes Responsible For Yeast Competencementioning
confidence: 99%
“…Rossini et al (1 993) reported environmental factors affecting protein release into the medium, as was also found in penetration of chemical fixatives into cells (Vogel et al, 1992). Passage of DNA into cells has been shown to be improved following treatment with the glucan synthase inhibitor, Aculeacin A (Gallego et al, 1993) whereas EDTA, mercaptoethanol and proteinase K were shown to facilitate release of chromosomes (Gardner et al, 1993).…”
Section: Permeabilitymentioning
confidence: 99%
“…A eficiência da transformação é também intluênciada pelo tipo e conformação do plasmídio. É sabido que os plasmídios integrativos transformam seus hospedeiros com baixa eficiência, comparados com moléculas de replicação autônoma (1 transf.lJLg de DNA plasmidial), (BEGGS, 1978;GALLEGO et al, 1993), porém quando estes são linearizados produzem maior número de transformantes. KASUSKE et alo (1992) (HIEP et ai., 1993).…”
Section: Vetores De Clonagemunclassified
“…Seguem as estapas de lavagem e estocagem. Alguns autores acreditam que a baixa eficiência de transformação é devida ao marcador seletivo utilizado (HIEP et al, 1993;GALLEGO et al, 1993), outros desmonstram que a conformação do plasmídio favorece o processo (VIDAL & GARBER, 1994) porém, existem outros que defendem a possibilidade de que o método empregado tem importância relevante no processo de transformação (MEILHOC et al, 1990;KASUKE et al, 1992) principalmente quando associados a alguns parâmetros, as quais podem gerar transformantes em um curto espaço de tempo (HIGGNS & STRATHERN, 1991 Apesar dos resultados acima, a transformação ainda apresentou-se com baixa eficiência e isto pode ser devido ao método empregado para a preparação da célula receptora, onde as células intactas ou esferoplastizadas podem ser utilizadas. A parede celular tem uma influência marcante na competência da célula para introdução do DNA, sendo que a eficiência é aumentada quando se trabalha com células esferoplastizadas (BEGGS, 1978).…”
Section: Avaliação Da Estabilidade Mitótica Dos Plasmfdiosunclassified